Problematyka następstwa prawnego mortis causa kont na platformach dystrybucji cyfrowej gier komputerowych - Trzpis, Kamil (Wydawnictwo C.H. Beck, 2022)
The purpose of this paper is to discuss the issue of inheritance of deceased users’ accounts on digital distribution plat-forms of computer games by heirs. The study assesses the applicable inheritance regulations from the point of view of the possibility of their application to digital goods in this form. The author presents examples of solutions used by selected platforms. He also raises issues of secrecy of the testator’s and third party correspondence conducted on such platforms. Finally, the author takes a position on the issue and formulates postulates de lege ferenda.
Keywords: inheritance of accounts on digital distribution platforms; digital goods; electronic games; correspondence secrecy; inheritance